Dampak Pengembangan Eko Wisata Berkah Pantai Tapandullu Terhadap Peningkatan Perekonomian Masyarakat di Desa Tapandullu Kecamatan Simboro - ratna, ratna; Heryati, Yati (GROWTH Jurnal Ilmiah Ekonomi Pembangunan, 2022)
This research takes the title Impact of Ecotourism Development Blessings of Tapandullu Beach on Community Economic Improvement in Tapandullu Village, Simboro District. The purpose of this research is to determine the impact of the development of Eco Tourism Blessings of Tapandullu Beach on the economy of the community in Tapandullu Village, Simboro District. The results of research and discussion on the impact of developing eco-tourism with the blessing of the Tapandullu beach on the economy of the community in Tapandullu Village, Simboro District, concluded that the development of Eco-tourism with the blessing of the Tapandullu beach has a positive impact on income, namely people who work in tourist areas as food, beverage traders and wood craftsmen who work in the tourism area. services used for the manufacture of tourist facilities have increased economic income. Village infrastructure is an access road to the village there is a change in the form of road repairs. Furthermore, the West Sulawesi Provincial Government paid more attention to the previous area and made Tapandullu Village easy to reach by four-wheeled vehicles. Then increase the number of visitors, develop and improve tourist attraction facilities. So that with this increase, visitors will be more comfortable and interested in traveling on the Tapandullu beach.